Farmer-Developed Varieties as Innovations – The Case of Kunjukunju Rice Cultivar from Kerala (Journal of Intellectual Property Rights (JIPR), 2026)
Farmers have been continuously contributing to evolving crop varieties that fit specific locations and changing conditions. There are different possibilities for recognizing farm innovations in India. The Biological Diversity Act ensures equitable sharing of benefits to the conservers of biological resources, their by-products, creators or holders of traditional knowledge, innovations and practices associated with such resources. The National Innovation Foundation scouts and supports grassroots innovations that have been developed without any help from a formal sector. The country also has the Protection of Plant Varieties and Farmers’ Rights Act, which offers legal protection to its Plant Genetic Resources for Food and Agriculture. This sui-generis legislation for plant variety protection has a unique component: Farmer’s Rights, which facilitates the recognition of crop varieties conserved and developed by farmers or farming communities, along with other provisions. This article examines the opportunities and challenges of these legislations, taking the case of Kunjukunju, a rice cultivar from Kerala that is claimed to have been ‘developed’ by a farmer innovator 50+ years ago and which lacks evident and documented information. The methodology adopted for this case analysis could be a promising one for inquiring about and resolving such concerns regarding the rights over Plant Genetic Resources.